Vernon God Little - Pierre, D. B. C. (faber and Faber, 2012)
In a small Texas town, fifteen-year-old Vernon finds himself in trouble after his best friend Jesus kills sixteen of his classmates before committing suicide, as he becomes the target of vengeful townspeople and the media.